Ritual Wulla Poddu Sebagai Model Resiliensi Masyarakat Marapu di Kampung Tarung dan Praiijing Sumba Barat - Berlian Rambu Pesi Kondi; Rama Tulus Pillakoannu; Izak Y. M. Lattu (Universitas Negeri Medan, 2021)
The purpose of this research is to analyze the Wulla Poddu ritual as Resilience Model of Marapu community in Tarung and Praiijing villages, West Sumba. The theories used are resilience, ritual, and liminal.The research approach is descriptive qualitative method. The deep data is obtained based on the understanding of the community informants. The results of the research showed that under a lot of pressures, Tarung and Praiijing community had the ability to return to the beginning of the situation called resilience in the form of Wulla Poddu ritual of Marapu belief. Marapu is considered as the intermediate spirit that had the power to raise the feeling of the community through Wulla Poddu ritual events. The Wulla Poddu Ritual bound the community to be one unity without status and religious differences, and returned to live their life as the beginning and even better than before. The pressure and uncertainty came from the government in obtaining rights, responsibility, and official religions (Islam and Christian) where the fact shows that they have a belief in Marapu as their God. In this case, the Wulla Poddu becomes an open ritual of uncertainty.